A beautiful day in the neighborhood [videorecording (Blu-Ray + DVD)] - Fitzerman-Blue, Micah, 1982-; Harpster, Noah, 1976-; Harpster, Noah, 1976-; Hanks, Tom; Rhys, Matthew, 1974-; Watson, Susan Kelechi, 1981-; Cooper, Chris, 1951-; Lahti, Christine; Makkena, Wendy; Colantoni, Enrico, 1963-; Blanchard, Tammy (Sony Pictures Home Entertainment, 2020)
Tom Hanks portrays Mister Rogers in a timely story of kindness triumphing over cynicism, based on the true story of a real-life friendship between Fred Rogers and journalist Tom Junod. After a jaded magazine writer is assigned a profile of Fred Rogers, he overcomes his skepticism, learning about kindness, love, and forgiveness from America's most beloved neighbor.